Вплив компонентів, які входять до складу плазмозамінників (електролітів і сорбіту), на активність іммобілізованої холін естерази - Payentko, V. V.; Matkovsky, A. K.; Matrunchik, Yu. V.; Zub, Yu. L. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2012)
It has been studied how the cholinesterase activity of immobilized cholinesterase is influenced by components containing in such plasmasubstitutes as Sorbilact and Reosorbilact. Fixation of ferments has been carried out by it's introduction in the silica gel structure during sol–gel transformation in the presence of hydroaccumulating complex (polyacryl acid polyvinyl alcohol). Differently from earlier described characteristics of components of plasmasubstitutes to activate the native cholinesterase, the times 1.5 decrease in activity of ferment with the twice increasing of sorbitol concentration for immobilized cholinesterase has been shown.